Estudo comparativo do desempenho muscular isocinético do quadril de jovens e idosos utilizando um dispositivo estabilizador - Alexandre de Oliveira (2006)
The elderly population in Brazil has been increasing in an accelerated manner in the past few years, and it is expected to increase even more in the coming years. Along with the ageing process functional losses occur, such as the decrease of muscular performance, which has a direct impact in the activities of daily living, such as walking, for instance. Muscular performance assessments are extremely important and a joint that deserves a special attention is the hip, due to the relationship that it has with many functional daily activities. The knowledge of values of hip performance may contribute to the creation of treatment protocols for the elderly population, as well as contribute to the identification of possible injury risks. The objective of the present study was to identify isokinetic hip muscular performance values, and make a comparison between the elderly and the young, and also to check the reliability of a stabilization frame specially built for the present study. 59 phisically active volunteers participated in the present study: 15 young women and 15 young men, being between 20 and 30 years old and 15 elderly women and 14 elderly men, being 65 years old and older. A stabilization frame was specially built for this study, so that when attached to the isokinetic dynamometer Biodex System 3 Pro® it would allow for a safe hip assessment in the standing position, offering biomechanical safety and stability. The reliability of this stabilization frame was checked by a pilot study with 10 volunteers, being 5 young and 5 elderly. In the present study the following variables were evaluated: work, at the angular velocity of 60°/s, power, at the angular velocity of 120°/s and agonist-antagonist ratio, at the angular velocity of 60°/s, for the hip movements of flexion, extension, abduction, adduction, internal rotation and external rotation. Statistical analysis was performed with the software SPSS for Windows version 13.0 and since the results were not normally distributed a non-parametric analysis was performed with the Mann-Whitney test. Considering the agonist-antagonist ratio the elderly volunteers did not present statistically different values from the young group, which means that muscle balance at the hip joint was maintained in this group of elderly individuals. The elderly group displayed lower values of power at 120°/s and work at 60°/s in comparison to the young group, despite the fact that the agonist-antagonist ratio was preserved. The hip flexors and abductors were the muscle groups that presented the greatest proportional losses in total work and power when comparing the elderly to the young group. The results found in the present study are different from some results found in other studies that also evaluated the hip joint at the isokinetic dynamometer at the standing position. Probably the main reason for this is the difference in the design of the stabilization frame that was used in each study, considering the fact that only the one used in the present study was directly attached to the dynamometer´s seat. The stabilization frame that was developed and used in the present study proved itself to be adequate for the assessment of the studied population, as well as more indicated than the stabilization frames of the other studies to assess the hip in the upright position. This can be stated because the frame of the present study was directly attached to the dynamometer, no modification was made to the original settings of the dynamometer itself, and this frame allowed for the flexion, extension, abduction and adduction tests to be performed in the upright position.